Phytoecdysteroids from the Stem Bark of Vitex doniana and Their Anti-Inflammatory Effects - Ochieng, Charles O.; Ishola, Ismail O.; Opiyo, Sylvia A.; Manguro, Lawrence A.O.; Owuor, Philip O.; Wong, Keng-Chong (Planta Medica, 2013)
With reference to the ethnopharmacological significance of Vitex doniana Sweet (Lamiaceae) leaves in the treatment of stomach and rheumatic pains as well as inflammatory disorders, biological studies on its stem bark extracts have also reported anti-inflammatory and analgesic activities, with no attempt to identify the active components. Chromatographic and spectroscopic procedures identified three new phytoecdysteroids: 21-hydroxyshidasterone (1), 11β-hydroxy-20-deoxyshidasterone (2), and 2,3-acetonide-24-hydroxyecdysone (3) from the stem bark methanol extracts along with known ecdysteroids shidasterone (4), ajugasterone C (5), 24-hydroxyecdysone (6), and 11β,24-hydroxyecdysone (7). The compounds (1–7) showed significant (p ≤ 0.05) inhibitory effect at 100 mg/kg dose on rat paw oedema development due to carrageenan-induced inflammation in Sprague Dawley rats. These results suggest a possible contribution of ecdysteroids to the anti-inflammatory effect of some V. doniana stem bark extracts.
Keywords: Vitex doniana; Lamiaceae; anti-inflammatory; 21-hydroxyshidasterone; 11-hydroxy-20-deoxyshidasterone; 2,3-acetonide-24-hydroxyecdysone